PERAN MEDIASI KEPUASAN KERJA PADA GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PT. MAKMUR TECHNOLOGY INDONESIA - Muhammad Eryan Pratama; Siti Kholifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The mediating role of job satisfaction in the relationship between transformational leadership and employee performance at PT. Makmur Technology Indonesia is discussed in the context of the importance of the manufacturing industry to economic growth. Employee performance is considered crucial to a company’s competitiveness and is influenced by the leadership style employed. Job satisfaction, which refers to employees’ attitudes towards their work, has a significant impact on performance. Transformational leadership is proposed as a solution to improve performance through inspiration, creativity, and attention to the individual needs of employees, which in turn contributes to job satisfaction and overall company performance. This study aims to analyse the influence of transformational leadership on employee performance at PT. Makmur Technology Indonesia.In this study, the author employs a quantitative and associative research approach. The data collection techniques in this study were non-test methods (questionnaires and observation). The data analysis techniques in this study included validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, t-tests, F-tests, and coefficient of determination tests. The results of the study indicate that the analysis shows that Transformational Leadership (X) has a positive and significant influence on Job Satisfaction (Z). The regression coefficient of 0.241 indicates that a one-unit increase in Transformational Leadership will increase Job Satisfaction by 0.989 units. This effect is significant with a p-value of 0.006 (p < 0.05). Although the effect is relatively small (R-squared = 75.1%), this relationship is statistically significant.